Operowanie językiem w poszukiwaniu sensu oryginału - Tanuszewska, Lidia (Poznańskie Spotkania Językoznawcze, 2015)
This article is about the translation as a process which changes the way of thinking in the other language, the one in which we translate. In order to make that text understandable for readers, the translator needs to make some changes in the original text, i.e. to manipulate with the language, so that the translation will transfer the same meaning and sense of the original one. Paraphrase is one of the strategies that is presented in this work.